The menopause brain : new science empowers women to navigate menopause with knowledge and confidence - Mosconi, Lisa (Avery, an imprint of Penguin Random House, 2024)
"Menopause and perimenopause are still a black box to most doctors, leaving patients exasperated as they grapple with symptoms ranging from hot flashes to insomnia and brain fog. As a leading neuroscientist and women's brain health specialist, Dr. Lisa Mosconi unravels the mystery by revealing how menopause doesn't just impact the ovaries-but it's a hormonal show in which the brain takes center stage. The decline of the hormone estrogen during menopause influences everything from body temperature to mood and memory, potentially paving the way for cognitive decline later in life. To conquer these successfully, Mosconi brings us the latest approaches-from cutting-edge hormone replacement therapies like "designer estrogens" to the role of hormonal contraception, and key lifestyle changes encompassing diet, exercise, self-care, and self-talk. Best of all, Mosconi dispels the myth that menopause signifies an end, demonstrating that it's actually a transition. Contrary to popular belief, if we know how to take care of ourselves during menopause, we can emerge with a renewed, enhanced brain-ushering in a meaningful and vibrant new chapter of life"--